'A teacher's hug can make you feel better': listening to U.S. children's voices on high-quality early childhood teaching. Issue 4 (3rd July 2020) - Rodríguez-Carrillo, Julia; Mérida-Serrano, Rosario; González-Alfaya, María Elena
ABSTRACT: Shown to be the single most influential factor in children's early learning and development experiences, quality in early childhood education and care (ECEC) teaching has attracted increasing interest in research and policy globally. Yet almost all definitions of quality ECEC teaching to date reflect only adults' notions of the features that should define a good early-years professional. The present study captures children's (four-to-six-year-olds') voices on the knowledge, skills, and attitudes they believe a high-quality ECEC teacher should have. Two major categories emerge from the children's drawings and narratives, which illustrate children's perspectives on the quality of their teachers' role: (1) a teacher who adapts to the culture of childhood, and (2) a teacher who attends to individual diversity. Findings provide alternative measures of quality ECEC teaching grounded in children's thoughtful ideas about the ways they believe their teachers can have a positive impact on their school lives.